A comparative analysis of linear regression, neural networks and random forest regression for predicting air ozone employing soft sensor models - Zhou, Zheng; Qiu, Cheng; Zhang, Yufan (Scientific reports, 2023)
The proposed methodology presents a comprehensive analysis of soft sensor modeling techniques for air ozone prediction. We compare the performance of three different modeling techniques: LR (linear regression), NN (neural networks), and RFR (random forest regression). Additionally, we evaluate the impact of different variable sets on prediction performance. Our findings indicate that neural network models, particularly the RNN (recurrent neural networks), outperform the other modeling techniques in terms of prediction accuracy. The proposed methodology evaluates the impact of different variable sets on prediction performance, finding that variable set E demonstrates exceptional performance and achieves the highest average prediction accuracy among various software sensor models. In comparing variable set E and A, B, C, D, it is observed that the inclusion of an additional input feature, PM 10 , in the latter sets does not improve overall performance, potentially due to multicollinearity between PM 10 and PM 2.5 variables. The proposed methodology provides valuable insights into soft sensor modeling for air ozone prediction.Among the 72 sensors, sensor NN R[Y]C outperforms all other evaluated sensors, demonstrating exceptional predictive performance with an impressive R 2 of 0.8902, low RMSE of 24.91, and remarkable MAE of 19.16. With a prediction accuracy of 81.44%, sensor NN R[Y]C is reliable and suitable for various technological applications.